Early Detection Score of Preeclampsia Risk - Dhiana Setyorini, - (Medico Legal, 2019)
Preeclampsia (PE) is a specifi syndrome during pregnancy that only occurs after 20 week of pregnancy, signed by high blood pressure, edema, and protein in the urine. In the method of this present research, at the fist stage, a case control design consisting of 704 pregnant women was analyzed using the multinomial logistic regression. At the second stage, scoring cards were set up based on the OR value and was continued with the “panel expert” attended by 10 informants to perfect the scores. At the third stage, a try-out was made using a cross sectional design for 110 pregnant women, and Mc Nemar Test was employed to analyze the results. The cross section, sensitivity, and specifiity were analyzed with ROC curve. Signifiant variables of PE risks were history of DM, obesity, history of hypertension, age, PE descent, multigravida, and incomes. From the results of the analysis, the Mc Nemar test was 90.9%, cross section was 7.5, sensitivity was 96.8% and specifiity was 79.7%. Scoring card for the early detection of the PE risk is effective for detecting preeclampsia early.